Characteristics of stunted toddlers in Medan Belawan - Febrianti, Rifka; Tarigan, Renita Br.; Gulo, Riska; Silalahi, Marlinang Isabella; Simangunsong, Pahala Maringan Jubel; Pane, Putri Yunita (Buletin Kedokteran & Kesehatan Prima, 2025)
This study aimed to characterize stunting among children under five years of age in Medan Belawan, North Sumatra, Indonesia, a sub-district with a high prevalence of this public health challenge. Employing a quantitative descriptive design, data were retrospectively collected from records of 40 stunted toddlers at the Belawan Community Health Center in 2024. The analysis examined maternal and parental characteristics, as well as the demographic and anthropometric profiles of the toddlers, including gender, age, weight, height, and nutritional status. The results indicated that the demographic profile was predominantly composed of mothers with lower educational attainment, most having completed only junior or senior high school. Parental occupations were mainly homemakers and fishermen, reflecting the local socioeconomic context. Stunting was more common among male toddlers (57.5%) and those in the older age group (2.6–5 years), who accounted for 70% of the sample. Anthropometric measurements confirmed the severity of stunting, with 55% of toddlers classified as severely stunted and a significant proportion identified as underweight or severely underweight. Despite the high prevalence of stunting, the majority of toddlers were classified as well-nourished based on weight-for-height indices, suggesting that chronic growth failure rather than acute malnutrition constitutes the primary nutritional concern. These findings underscore the multifactorial and complex nature of stunting in this vulnerable population, emphasizing the roles of socioeconomic and environmental determinants beyond mere caloric deficiency.